Resocjalizacja i dziedzictwo instrumentalnej racjonalności - Sztuka, Mariusz (Horyzonty Wychowania, 2009)
The text takes up the issues of the rationality of resocialization as a field of social practice and the rationality of pedagogically orientated theory of corrective influences upon socially demoralized people. The context for deliberations presented is an argument about the role and meaning of instrumental rationality (referring to the relations between the means and goals of practical action) in pedagogy, being a manifestation of a critical reflection on the legacy of the Enlightenment idea. Reducing the problem to the level of methodological deliberations, the text constitutes an attempt to reconstruct the dominating on the grounds of Polish resocialization thought cognitive orientation in comparison with the redefinitions of paradigmatic nature taking place in the sphere of the general theory of education. A question arises in this context; it concerns the arguments which would call for broader adoption by resocialization pedagogy of the research perspective connected with the idiographic approach, thus the question concerns the need, scope, conditions and opportunities of undertaking quality research. The author opts for a solution which treats the issue of placing methodological perspectives in recognizing reality described by the theory of resocialization first and foremost as a problem of proportions marked by the specificity of the reality being recognized. A mode of conduct based on this assumption, compared to the events requiring recognition – and these in resocialization take the form of tangible, usually notable and marked by regularity social facts – adopts a strategy of quantity empirical research, and at the same time opens a possibility to penetrate these problem spheres, which do not fall into the determined pattern, go beyond the framework of quantity analysis, and thereby require an analysis based on the instrumentarium developed on the basis of the idiographic paradigm...